2014
DOI: 10.1063/1.4862331
|View full text |Cite
|
Sign up to set email alerts
|

Helium ion microscope generated nitrogen-vacancy centres in type Ib diamond

Abstract: We report on position and density control of nitrogen-vacancy (NV) centres created in type Ib diamond using localised exposure from a helium ion microscope and subsequent annealing. Spatial control to <380 nm has been achieved. We show that the fluorescence lifetime of the created centres decreases with increasing ion dose. Furthermore, we show that for doses >1 Â 10 17 ion/cm 2 , significant damage of the diamond lattice occurs resulting in fluorescence quenching and amorphization. This places an upper limit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
30
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 34 publications
0
30
1
Order By: Relevance
“…However, stochastic variation gives rise to the existence of a few NDs exhibiting domains with large numbers of spatially and spectrally identical NV centres which do act cooperatively.It should be noted that previous studies reported a decrease in the LT of NVs for centres produced via lowenergy He-ion irradiation, with the decay time decreasing for increasing ion doses. This effect has been attributed to increased damage in the crystal lattice which provides nonradiative decay paths with faster dynamics [15,16]. This is however inconsistent with our observations where we found that higher peak fluorescence correlated to faster decay rates (see Supplementary Information) -the exact opposite of what would be expected if the shortening of the LTs was indeed due to non-radiative, dark pathways.…”
contrasting
confidence: 95%
See 1 more Smart Citation
“…However, stochastic variation gives rise to the existence of a few NDs exhibiting domains with large numbers of spatially and spectrally identical NV centres which do act cooperatively.It should be noted that previous studies reported a decrease in the LT of NVs for centres produced via lowenergy He-ion irradiation, with the decay time decreasing for increasing ion doses. This effect has been attributed to increased damage in the crystal lattice which provides nonradiative decay paths with faster dynamics [15,16]. This is however inconsistent with our observations where we found that higher peak fluorescence correlated to faster decay rates (see Supplementary Information) -the exact opposite of what would be expected if the shortening of the LTs was indeed due to non-radiative, dark pathways.…”
contrasting
confidence: 95%
“…V dd (|e σ1 , g σ2 g σ1 , e σ2 |+|g σ1 , e σ2 e σ1 , g σ2 |) (15) where V dd = 3γb 4(nk 0 ∆r) 3 (d 1 ·d 2 − 3(d 1 ·n)(d 2 ·n)). (16) Hered j is the unit vector direction of the dipole j, ∆r = | r 1 − r 2 | is the separation,n = ( r 1 − r 2 )/∆r is the unit vector separation between dipoles, b ≈ 0.03 is the branching ratio to the ZPL [31], n = 2.4 is the index of refraction of the diamond crystal, γ is the optical decay rate which we can take as γ/2π = 5 MHz for the present estimate, and k 0 = 2π/λ 0 is the vacuum wavevector of the optical transition at wavelength λ 0 = 639nm.…”
Section: Theoretical Model and Fittingmentioning
confidence: 99%
“…Top-down approaches involve the creation of colour centres directly in bulk diamond using high-energy ion, neutron, or electron irradiation followed by annealing [23][24][25] . Implanting colour centres with nanoscale precision is a challenge, which can be overcome by using a lithographic mask 26,27 or a direct-write focussed beam 21,28 . Vertical distribution in the substrate is another challenge for direct writing techniques [29][30][31] , especially since the depth of the colour centre below the surface has an impact on the fluorescence and to sense things near the surface the the colour centres have to be proximal to the surface.…”
Section: Introductionmentioning
confidence: 99%
“…In principle, the HR1 emission lifetime should enable the detection of luminescence from individual defects, while the HR2 center is almost three times weaker in emission due to its relatively long lifetime. Overall, the narrow ZPL emission of HR centers with small phonon coupling and the photo-excitability under a wide spectral range, combined with the large availability of focused He beams for fabrication [16,[25][26][27] represent promising aspects for the application of HR defects in quantum technologies. …”
mentioning
confidence: 99%